Influence of psychological hardiness on academic achievement of university students: The mediating effect of academic engagement. - Meng, Qian; Jia, Wenxiu (Work, 2023)
BACKGROUND: The dropping out of university students is a serious problem faced by higher education all over the world. Studies have shown that academic hardiness is a positive psychological variable to prevent students from dropping out of university and academic burnout. Psychological hardiness can reduce the dropping out by increasing university students' academic engagement and academic achievement. OBJECTIVE: This study aims to discover the influence of psychological hardiness on university student's academic achievement and the mediating role of academic engagement in the relationship between psychological hardiness and academic achievement. A cross-sectional study was conducted among 615 participants. METHODS: Pearson correlation coefficients were conducted to analyze the relationships between psychological hardiness, academic engagement and academic achievement. Mediation analysis was used to evaluate the mediating role of academic engagement in the relationship between psychological hardiness and academic achievement. RESULTS: The research indicated a closely significant association between psychological hardiness, academic engagement and academic achievement. Psychological hardiness can directly predict academic achievement and can also indirectly predict academic achievement through the intermediary effect of academic engagement. CONCLUSION: This study could have important implications for research by linking psychological hardiness and academic achievement. The results suggest that universities should pay attention to the positive role psychological hardiness plays in improving university students' academic achievement. This study also benefits the university administrators, especially, those dealing with university students at the risk of dropping out and high academic stress.